Clinico-radiological correlation of osteoarthritis knee using Western Ontario and McMaster Universities score and Kellegren and Lawrance grading - Rajpoot, Manish Singh; Peepra, Digember; Pandey, Krishna Kumar; Varma, H. S. (International Journal of Research in Medical Sciences, 2016)
Background: Diagnosis OA is basically based upon clinical and radiological features. In our study we have used a clinical scoring system of OA called as WOMAC (Western Ontario and McMaster Universities) score and a radiological staging system KL staging (Kellegren and Lawrance) OA radiological staging system and correlation between them. Methods: There were total 66 patients with 102 knees. X ray of bilateral knee was taken in weight bearing position (standing) and WOMAC score was calculated. X-rays were assessed with KL grading. WOMAC score a clinical scoring was correlated with a radiological KL grading for the OA of knee. Results: Range of WOMAC score was 11.5-67.7. Mean WOMAC score were 18.75, 31.31, 52.57 and 67.2 in patients of KL grade 1, 2, 3 and 4 respectively. Correlation between KL grading and WOMAC scoring were found to be significant; there were rise in the WOMAC scoring when KL grading increases. Conclusions: Both the KL grading and WOMAC score are directly proportional to each other, and hence, WOMAC scoring can be used to diagnose, assess the progression of the disease and the response to treatment of osteoarthritis.